Pembenahan Tata Kelola Ikatan Ahli Boga Dewan Pengurus Cabang Kabupaten Lombok Barat - Hermanto Hermanto; Thatok Asmony; Prayitno Basuki (Jurnal Gema Ngabdi, 2020)
The activity of improving the governance of the Ikaboga Branch Management Board (DPC) of West Lombok Regency aims to provide knowledge for the administrators of the Ikaboga DPC, West Lombok Regency regarding good organizational governance. Another objective of this activity is to provide knowledge on how to compile financial reports, especially bookkeeping and provide training to make financial reports for administrators so that the organization becomes good governance. In the end, this activity is expected to provide an understanding for the administrators of the Ikaboga DPC, West Lombok Regency about how good governance and the administrators of the Ikaboga DPC in West Lombok Regency are able to manage finances and make financial reports so as to improve better governance. This training activity will be aimed at administrators of the Ikaboga DPC, West Lombok Regency. The implementation of activities is carried out with the approach of providing material relevant to improving governance.